2009
DOI: 10.1177/0363546509349055
|View full text |Cite
|
Sign up to set email alerts
|

Shallow Medial Tibial Plateau and Steep Medial and Lateral Tibial Slopes: New Risk Factors for Anterior Cruciate Ligament Injuries

Abstract: A combination of increased posterior-directed tibial plateau slope and shallow medial tibial plateau depth could be a major risk factor in anterior cruciate ligament injury susceptibility regardless of gender. Different injury risk models may be needed for men and women as other key risk factors are identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

29
481
10
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 345 publications
(529 citation statements)
references
References 29 publications
29
481
10
3
Order By: Relevance
“…However, it is unclear why such a difference was not observed among women. A similar inconsistency was reported by Hashemi et al, in which the male's medial PTS was associated with injury but not the female's [21]. They also observed an increased medial tibial plateau depth in conjunction with an increased PTS in patients with noncontact ACL injuries and concluded an increased medial plateau depth as an important risk factor (odds ratio, 3.03), followed by the medial (odds ratio, 1.18) and lateral (odds ratio, 1.17) PTSs [21].…”
Section: Discussionsupporting
confidence: 73%
See 4 more Smart Citations
“…However, it is unclear why such a difference was not observed among women. A similar inconsistency was reported by Hashemi et al, in which the male's medial PTS was associated with injury but not the female's [21]. They also observed an increased medial tibial plateau depth in conjunction with an increased PTS in patients with noncontact ACL injuries and concluded an increased medial plateau depth as an important risk factor (odds ratio, 3.03), followed by the medial (odds ratio, 1.18) and lateral (odds ratio, 1.17) PTSs [21].…”
Section: Discussionsupporting
confidence: 73%
“…Although some studies relied on the use of the medial PTS, Stijak et al [46] focused on the lateral PTS and reported only a greater lateral PTS promotes injury. However, they also found a greater medial PTS in the control group versus the injured group which contradicts the data of three other studies [8,21,47]. Stijak et al [46] hypothesized that, under normal loading conditions, patients with a greater lateral PTS may have greater internal rotations of the lower leg.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations